Live poles for slope stabilization in the tropical environment - Mafian, Sasan; Kim Huat, Bujang; Barker, David H.; A. Rahman, Nordin; Singh, Harwant (Electronic Journal of Geotechnical Engineering, 2009)
Slope instability causing landslides, a major geologic hazard, is a risk common to most regions. Among all categories of landslides, shallow slope failures which affect many hill slopes and earthwork projects are the most wide spread and pose the most costly maintenance problem. One of the soil improvement methods that seem suitable for shallow slope failures is the Live Pole technique. The potential value of this bioengineering technique is that it offers an effective, economical and environmentally favorable means of combating the predicted future increase in shallow slope instability by reinforcing slope shoulders, conducting drainage of horizontal groundwater and acting as surface flow retardation or energy dissipaters, to control slope erosion. Moreover the growth of live pole roots provides shear strength enhancement and modifies the saturated soil water regime. Due to the geographical variability in the application of this technique in different regions this study was carried out for a tropical environment. This paper initially describes the bioengineering technique for slope stabilization and the requirement for selecting suitable live poles in tropical regions utilizing indigenous woody species. These plants put through screening tests trials for the potential of the species to propagate from large live cuttings obtained from branches of small trees and shrubs tests, viz., tests for root and stem growth in a controlled medium under controlled shade-house conditions with irrigation, mechanical tests and then gauge their suitability for field trails by replanting in selected natural soils. Then results of these screening tests found two species, namely, Hibiscus tiliaceus (Ht) and Dillenia suffructicosa (Ds) which met the requirements for field test trials. For field tests they were installed using a twoman auger in a close center array on selected trial slopes in the University Putra Malaysia (UPM) campus and monitored for about 1 year. Some of these planted poles were studied and tested after exhumation at the end of this period and the results are discussed. This research shows that live poles are a practical and economical alternative method to conventional techniques for shallow-seated hill slope stabilization.